2017
DOI: 10.5539/elt.v10n10p50
|View full text |Cite
|
Sign up to set email alerts
|

Effective Behavior of EFL Teachers as Perceived by Undergraduate Students in Indonesia

Abstract: This study attempts to explore the effective behaviors of teachers of English as a foreign language (EFL) as perceived by undergraduate students in Indonesia. For this purpose, a questionnaire was administered to 270 Indonesian undergraduate students. The questionnaire addressed seven dimensions of EFL teachers’ behavior, which are the following: encouraging contact between students and teachers; developing reciprocity and cooperation among students; encouraging active learning; giving prompt feedback; emphasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…These following studies also revealed that there were differences in the students' perceptions of the qualities possessed by English teachers (Barnes & Lock, 2010Bell, 2005;Brosh, 1996;Çelik et al, 2013;Hidayat, 2017;Karim, 2021;Khaerati, 2016;Kwangsawad, 2017;Mudra, 2018;Park & Lee, 2006;Said, 2017;Shishavan & Sadeghi, 2009). These studies indicate that the conceptions among people toward effective NNETs were proved to be different depending on levels of schooling, curriculum, gender, major area, and background.…”
Section: Relevant Studiesmentioning
confidence: 80%
See 1 more Smart Citation
“…These following studies also revealed that there were differences in the students' perceptions of the qualities possessed by English teachers (Barnes & Lock, 2010Bell, 2005;Brosh, 1996;Çelik et al, 2013;Hidayat, 2017;Karim, 2021;Khaerati, 2016;Kwangsawad, 2017;Mudra, 2018;Park & Lee, 2006;Said, 2017;Shishavan & Sadeghi, 2009). These studies indicate that the conceptions among people toward effective NNETs were proved to be different depending on levels of schooling, curriculum, gender, major area, and background.…”
Section: Relevant Studiesmentioning
confidence: 80%
“…Studies on effective NNETs have largely taken into accounts the voices of various stakeholders, such as teachers, schools, and administration staff (Bell, 2005;Brosh, 1996;Hidayat, 2017;Karim, 2021;Kwangsawad, 2017;Park & Lee, 2006;Shishavan & Sadeghi, 2009). However, little is known about effective NNETs as represented in students' voices (Barnes & Lock, 2010Çelik et al, 2013;Khaerati, 2016;Mudra, 2018;Said, 2017). It is in line with Tarone and Allwright (2005), as well as Tsui (2011), who claim that research on English teachers has made little reference to students, and if existed, students' voices have largely remained silent.…”
Section: Introductionmentioning
confidence: 99%
“…Subject matter knowledge in this study includes knowledge of the English language and language components. Since English is the subject matter of foreign language teaching, language proficiency and communicative ability in English is a necessary pre-requisite for a language teacher (Richards, 1997). Apart from the teachers' capability, mastery of subject matter knowledge has a close relationship with the teacher educators' professionalism (Amin, 2013: 72).…”
Section: The Perceptions Of the Subject Matter Knowledgementioning
confidence: 99%